STRATEGI REKRUTMEN PESERTA DIDIK BARU MELALUI SISTEM PENERIMAAN MURID BARU (SPMB) PADA SEKOLAH MENENGAH KEJURUAN: STUDI LITERATUR - Safitri Nasution, Aulia Helen; Hinggil Permana; Lau Han Sein (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article aims to analyze new student recruitment strategies through the New Student Admission System (SPMB) in vocational schools. The issue is important because vocational schools face increasing competition, changing public preferences, and stronger demands for transparent and accountable admission services. This study used a literature study method with a descriptive qualitative approach. Data sources were selected from previous studies and theoretical references related to educational management, school marketing, student recruitment, and SPMB. The data were analyzed through identification, classification, comparison, and synthesis of findings from relevant literature. The results show that an effective recruitment strategy through SPMB requires four integrated stages, namely planning, organizing, implementation, and evaluation. Planning includes target setting, quota analysis, admission criteria, promotional design, and preparation of the SPMB committee. Implementation includes school promotion, information services, registration, document verification, selection, announcement, and re-registration. Evaluation is needed to measure the achievement of admission targets, service quality, media effectiveness, and barriers during the admission process. The study also found that school reputation, program quality, digital promotion, community support, facilities, and government policy influence recruitment success. Therefore, SPMB should not be viewed only as an administrative procedure, but as a strategic instrument to strengthen school competitiveness and public trust.